Inclusion of Biuret With or Without Bovatec in a Commercial Mineral Supplement Did Not Improve Growth Performance of Yearling Calves Grazing Native Grass: Year 1 of 2 - M. G. Pflughoeft; Z. M. Duncan; Z. L. DeBord; K. J. Suhr; W. R. Hollenbeck; F. K. Brazle; A. J. Tarpoff; K C Olson; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this experiment was to measure the effects of non-protein nitrogen (NPN; biuret) or NPN + ruminal modifier (biuret + Bovatec, Zoetis, Parsippany, NJ) inclusion in a commercial mineral mix on growth performance of yearling beef calves grazing in the Kansas Flint Hills. Study Description:Three hundred ninety-five crossbred steers (initial body weight: 612 ± 77.8 lb) of Texas origin previously backgrounded at the Kansas State University Beef Stocker Unit were used. Three mineral treatments consisting of a basal supplement (control), a basal supplement plus NPN (biuret), and a basal supplement plus NPN and lasalocid (Bovatec) were provided with a 4 oz/head/day mineral consumption target. The three mineral treatments were randomly assigned to one of 18 pastures with a total of six pastures per treatment. Feeders were checked daily to determine days-to-empty and were weighed weekly to determine mineral consumption. Individual weights were collected at the start and end of the 90 days to determine initial and final body weights (BW). Results:There was no difference (P≥ 0.31) in final BW, total BW gains, average daily gains, and mineral consumption between mineral treatments. For days-to-empty, there was an interaction between treatment and week of the experiment (P= 0.02). The bottom line:The data were interpreted to suggest that the addition of biuret or biuret and lasalocid to a commercial mineral supplement did not affect growth performance of yearling beef cattle grazing in the Kansas Flint Hills.
Keywords: stocker; grazing; non-protein nitrogen